2021
DOI: 10.1111/epi.17131
|View full text |Cite
|
Sign up to set email alerts
|

Rasmussen encephalitis: Predisposing factors and their potential role in unilaterality

Abstract: Objective: Rasmussen encephalitis (RE) is a progressive and destructive inflammatory disease of one hemisphere. Its cause is unknown. We investigated comorbidity and laterality factors that might predispose to RE. Methods:We retrospectively compared the histories of 160 RE patients to those with genetic generalized epilepsy (n = 154) and those with focal cortical dysplasia Type II (FCD II; n = 148). Results:The median/mean age at symptom onset in RE was 7/10 years (range = 1-53 years), and 58.1% of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…Similar to clinical evolution, RE also evidences a neuropathological progression, dealing with four stages with the progressive cortical injury sustained by T-lymphocyte and neuroglial activation [ 19 ]. A retrospective series of 160 RE cases showed that perinatal complications and other autoimmune conditions (like scleroderma, uveitis, and chorioretinitis) might predispose to RE [ 27 ]. Treatment in RE syndrome aims to reduce seizure frequency and improve motor and long-term cognitive outcomes.…”
Section: Rasmussen’s Encephalitismentioning
confidence: 99%
“…Similar to clinical evolution, RE also evidences a neuropathological progression, dealing with four stages with the progressive cortical injury sustained by T-lymphocyte and neuroglial activation [ 19 ]. A retrospective series of 160 RE cases showed that perinatal complications and other autoimmune conditions (like scleroderma, uveitis, and chorioretinitis) might predispose to RE [ 27 ]. Treatment in RE syndrome aims to reduce seizure frequency and improve motor and long-term cognitive outcomes.…”
Section: Rasmussen’s Encephalitismentioning
confidence: 99%
“…Posterior al desarrollo de la EPC su hemiparesia secuelar empeoró y se acentuó un poco más tras la cirugía. Respecto a ello, se ha descrito que lesiones cerebrales unilaterales adquiridas a temprana edad son más frecuentes en pacientes con ER comparados a pacientes sanos y que estas lesiones son ipsilaterales al hemisferio afectado por ER (15). De la misma forma, la paciente 3 presentó 2 lesiones identificadas en las neuroimágenes, sin que estas patologías pudieran explicar su cuadro clínico; pues los angiomas venosos no suelen asociarse al desarrollo de epilepsia y las calcificaciones residuales no se asocian a epilepsia farmacorresistentes; en ambos casos podrían ser silentes.…”
Section: Discusionunclassified
“…In 2005, Bien et al proposed formal diagnostic criteria of the European consensus statement for RE, which described Part A and Part B 14 . The diagnosis of RE requires the fulfilment with either all three criteria of Part A or two out of three criteria of Part B. Scholars suggest that the positive histopathology (B3 in Part B) plus two of three A criteria could also be diagnosed as RE for improving the sensitivity of the criteria and this modified criteria was applied in a retrospective study by Bien 15,16 …”
Section: Introductionmentioning
confidence: 99%